Association between Oral Hygiene Knowledge, Attitudes, and Practices and OHI-S among Pregnant Women: A Cross-Sectional Study - Sadimin Sadimin; Hermien Nugraheni; Diyah Fatmasari; Agnes Lia Renata; Fitri Kusumasari (JURNAL INFO KESEHATAN, 2026)
Pregnant women are at increased risk of oral health problems, including dental caries and gingivitis. This study aimed to examine the association between oral hygiene knowledge, attitudes, and practices and oral hygiene status among pregnant women attending antenatal care at Sragi Health Center, Pekalongan Regency, Indonesia. A cross-sectional analytical study was conducted among 124 pregnant women selected using accidental sampling. Data on oral health knowledge, attitudes, and practices were collected using a structured questionnaire comprising 10 items per domain. Oral hygiene status was assessed using the Simplified Oral Hygiene Index (OHI-S). Associations between behavioral variables and OHI-S categories (good, moderate, poor) were analyzed using Kendall's Tau-B. Most participants had primary-level education (58%), good knowledge (58%), good attitudes (65%), and poor oral health practices (65%). Most respondents showed a moderate OHI-S status (61%). No significant association was found between educational level and OHI-S (p = 0.655). Significant associations were observed between knowledge and OHI-S (p = 0.017), attitudes and OHI-S (p = 0.010), and practices and OHI-S (p = 0.032). Knowledge, attitudes, and practices related to oral health were associated with oral hygiene status among pregnant women, whereas educational level was not significantly associated with OHI-S.